Atlantic Forest and Ferruginous Rocky Grasslands Environmental Offsetting in Minas Gerais, Southeastern Brazil : Between Legalism and Ecological Ineffectiveness - Nascimento, Alexandre Túlio Amaral; Mendes, Izabela Venceslau; Gonçalves, Renato Melo; Ferreira, Henrique Lua Santos; Santos, Érica Maria Freitas dos; Silva, Amanda Cristina Sena; Cristofoli, Gustavo Tofanin (Desenvolvimento e Meio Ambiente, 2025)
The Atlantic Forest (AF) is one of the world’s most threatened biodiversity hotspots and the only Brazilian biome ruled by a specific conservation law. The present study is an investigation about AF environmental offsetting (EO) in Minas Gerais State (MG), as provided for by the Brazilian environmental legislation. Minas Gerais State exceeds the provisions in the AF law and requires the compensate area to be twice as large as the cleared area. Although these instruments have the potential to help the biome’s ecological restoration, MG is always among the Brazilian states accounting for deforesting the AF the most. Data about 128 legal suits processed by MG’s environmental agency between 2020 and 2023 were analyzed. Most EO cases in MG regarded the tenure regularization of legally protected land. Only 19% cases regarded ecological restoration. The EO approach in MG is ineffective and disconnected from the best scientific practices and it leads to net biodiversity loss, mainly in ferruginous rupestrian fields or canga areas. Recommendations include adopting integrated or cumulative environmental assessment, and prioritizing ecological restoration to achieve strategic biodiversity gains or, at least, no biodiversity loss in AF territories.